Сравнительный анализ содержания элементов полезных растений из коллекций Донецкого ботанического сада НАН Украины - Остапко, И.Н. (Промышленная ботаника, 2003)
The research of element composition of the above-ground crops in 73 species of herbaceous plants of 19 families and 51 genera during the phase of budding – beginning of blossom was being held in the Donetsk Botanical Gardens, Nat. Acad. Sci. of Ukraine in the period of the years 1992-2002. As for their use, these plants belong to three economically beneficial groups: fodder, medicinal and vegetable. The results of investigation can be used for prognosticating the content of certain elements or their complexes in the groups of plants under investigation.